Optimizing Oil Palm Plantation Land in an Effort to Increase Productivity in Pandeglang Regency, Banten Province (Architecture Image Studies, 2026)
This study aims to map the productivity of oil palm plantations in Pandeglang Regency in 2023. The methods that used including GIS (Geographic Information System) analysis and a descriptive-quantitative approach. The research methods include GIS analysis to visualize and analyze spatial data, and a descriptive-quantitative approach to evaluate productivity levels based on available data. The GIS analysis stages include collecting spatial data from official sources like BPS and Department of Agriculture, processing the data using software such as ArcGIS, and field validation to ensure the data accuracy. Data that have been collected includes oil palm plantation area, administrative boundaries, and oil palm production data. From this research show productivity levels in various regions of Pandeglang Regency. The resulting productivity distribution map identifies areas with high and low production levels, providing important insights for decision-making. This research is expected to provide recommendations for increasing production efficiency and yields, such as improving cultivation techniques and resource management. With this approach, it is hoped that oil palm plantation productivity can be increased sustainably.